Agnieszka Osiecka’s Diaries and Notes as a Source for Research into the History of Girlhood - Wilk, Marcin (Acta Poloniae Historica, 2023)
This review article refers to the publication of six volumes of personal notes by Agnieszka Osiecka (1936–1997), one of the most popular Polish poets, a songwriter, director, and journalist of the second half of the twentieth century. The collection under review covers mainly the 1950s and provides a space for the search for one’s own identity. While referring to the recent edition and highlighting selected themes, this review article puts forward a perspective on the entire body of documents published between 2013 and 2021. A particular emphasis is placed on the importance of analysis of such egodocuments in girlhood studies.